Uma abordagem para captura automatizada de dados abertos governamentais - Ferreira, Juliana Sabino (Universidade Federal de São Carlos, 2017)
Currently open government data run an important job on regards to public transparency, besides being obligated by law. But most of this data are stored in non-standard ways, isolated and independent, making it very hard for its use by third party systems providers. This work proposes the creation of an approach for capturing this open government data in an automated way, allowing its use in various applications. For that a Web Crawler was built for the capture and storing of this open government data, as well as an API for making this data available in JSON format, that way developers can easily use this data on their application. We also performed an evaluation of the API for developers with different levels of experience.
Keywords: Dados Abertos Governamentais; Cidades Inteligentes; Web Crawler; Serviços de informação e Estado; Information services - Government policy; Comunicação na administração pública; Communication in public administration; Internet na administração pública; Internet in public administration; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO